The La Follettes of Wisconsin : Love and Politics in Progressive America - Weisberger, Bernard A., 1922- (Book collections on Project MUSE., 1994)
. An intimate portrait of the Progressive movement and the revealing, poignant story of a prominent American family, The La Follettes of Wisconsin will charm, fascinate, and entertain its readers.